Intestinal Persistence of Colonizing Escherichia coli Strains, Especially ST131-H30, in Relation to Bacterial and Host Factors. (3rd January 2022) - Johnson, James R; Clabots, Connie; Porter, Stephen B; Bender, Tricia; Johnston, Brian D; Thuras, Paul
Abstract: Background: Superior gut colonization may underlie the pandemic emergence of the resistance-associated H 30 subclone of Escherichia coli sequence type 131 (ST131- H 30). Little is known about the associated host and bacterial characteristics, or the comparative persistence of non-ST131 intestinal E. coli. Methods: Generic and fluoroquinolone-resistant E. coli isolates from volunteers' serial fecal samples underwent clonal analysis and extensive polymerase chain reaction (PCR)-based characterization (phylogroup, selected sequence types, virulence genes). Kaplan-Meier survival analysis and Cox proportional hazards survival analysis using penalized regression (a machine-learning method) were used to identify correlates of strain persistence. Results: Screening of 2005 subjects at the Minneapolis VA Medical Center identified 222 subjects (117 veterans, 105 human and animal household members) for longitudinal fecal surveillance. Analysis of their 585 unique-by-subject fecal E. coli strains identified multiple epidemiological, ecological, and bacterial correlates of strain persistence. ST131- H 30, a strong univariable correlate of persistence, was superseded in multivariable analysis by outpatient status, fluoroquinolone resistance, and diverse (predominantly iron uptake-related) virulence genes. Conclusions: ST131- H 30 exhibits exceptional intestinal persistence, possibly due to a combination of fluoroquinolone resistance and virulence factors, which may be primarily colonization factors. This identifies both likely contributors to the ST131- H 30 pandemic and potential targets for interventions against it. Abstract : During longitudinal fecal surveillance of veterans without current infection and their household members, ST131- H 30 exhibited exceptional intestinal persistence, possibly due to a combination of fluoroquinolone resistance and virulence factors, which may be primarily colonization factors.